Reverse genetics platform for tomato mottle mosaic virus: infectious clone construction and resistance screening in tomato - Thuy T. B. Vo; Marjia Tabassum; Bupi Nattanong; Hyo-Jin Im; Minkwan Kim; Li-Long Pan; Hee-Seong Byun; Hae-Ryun Kwak; Sukchan Lee (Molecular Biology Reports, 2026)

Rice panicle detection from unmanned aerial vehicle (UAV) imagery via image restoration and pseudo-depth prior - Pan Pan; Haochun Li; MingXia Li; Saiyang Xu; Zhihao Guo; Guoping Yu; Long Yi; Maomao Li; Guomin Zhou; Jianhua Zhang (Computers and Electronics in Agriculture, 2026)

Performing comprehensive nutrient recovery through the integration of selective electrodialysis with reverse osmosis by using synthetic swine wastewater - Jingwei Xu; Yahui Huang; Zhi-Long Ye; Xiaofang Pan; Yenan Li; Lifeng Lin (Desalination, 2026)

Hydroclimatic dynamics over the western Tibetan Plateau since the Last Glacial Maximum: A critical review - Kashif Hayat; Jianghu Lan; Peng Cheng; Haoran Li; Xingxing Liu; Jiansen Li; Xiaohui Wu; Long Pan; Dexiang Gan; Hong Yan; Youbin Sun (Earth-Science Reviews, 2026)

Domain-knowledge-guided deep learning for probabilistic precipitation downscaling over southeastern Tibetan Plateau - Dayang Li; Baoxiang Pan; Yuan Liu; Ashish Sharma; Yan Zhou; Yi Yao; Jun Yin; Long Yang (Journal of Hydrology, 2026)

Ferrihydrite sulfidation transformation reduces the mobilization of coexisting cadmium under anoxic conditions: Insights into the transformation mechanism - Xiaoming Zhao; Yifei Wang; Yu Song; Xu Ma; Ning Chen; Leo Ka Long Cheung; Ayetullah Tunc; Reza Deevsalar; Jinru Lin; Yuanming Pan; Haibo Li (Hydrometallurgy, 2026)

Hydrogeochemistry, source apportionment, and Monte Carlo-based health risks of heavy metals in a Carlin-type gold mining area of karst region, Southwest China - Qiguo Hu; Pan Wu; Xuefang Zha; Ke Wang; Ruixue Zhang; Bo Li; En Long (Environmental Pollution, 2026)

Environmental cadmium disrupts placental angiogenesis and fetal growth via enhancing m6A modification in Wwp2 - Cheng-Fang Sun; Ye-Xin Luo; Xin-Xin Zhang; Rui Pan; Yu-Xi Wu; Jia-Ying Chen; Xin-Run Wang; Lan-Lan Wu; Si-Ting Liu; Wei Chang; Zhi Yuan; Da-Min Zhu; et al. (Environmental Pollution, 2026)

Fermentation modulates wheat germ gliadin-based nanodelivery systems loaded with wheat bran polyphenols: Physicochemical properties, interaction mechanism, and functional performances - Ai-Mei Liao; Shao-Kang Yang; Meng-Yu Gao; Siyi Han; Long Pan; Jayani Chandrapala; Haiyan Gao; Dandan Zhai; Jun-Wei Chen; Na Liu; Peng Li (Food Bioscience, 2026)

Differential fouling behaviors of standard and monovalent-selective membranes by digestate-derived dissolved organic matter in selectrodialysis - Xiaofang Pan; Jingwei Xu; Yenan Li; Yahui Huang; Victor Nikonenko; Natalia Pismenskaya; Zhi-Long Ye (Water Research, 2026)

Resource-oriented volatile fatty acid production and in situ recovery from food wastewater via integrated biocarrier-membrane anaerobic fermentation - Bizhen Zeng; Yuechao Wang; Kai Chen; Tianyu Li; Zhenxiang Pan; Long Chen; Lan Yang; Hongtao Zhu (Resources, Conservation and Recycling, 2026)

Design and optimization of an autothermal solid oxide electrolysis cell reactor for efficient and economical solar-driven carbon dioxide reduction - Zihan Lin; Junjie Hou; Haoran Li; Qi Xia; Jiale Long; Zhouxin Pan; Muhammad Sajid Khan; Chen Chen (Journal of Cleaner Production, 2026)

Recombinant bovine αs1-casein as an enhanced precursor for sleep-promoting peptides: A structural, peptidomic, and molecular docking study - Long Pan; Lin-Lin Ding; Meng-Jia Song; Xiang-Li Mu; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Guang-Hai Yu (Food Bioscience, 2026)

Effects of depositional heterogeneity on cover-collapse sinkholes resulting from engineering dewatering in the Pearl River Delta (China): Risk assessment and early warning methodology - Long Jia; Yan Meng; Lujuan Li; Xiaolong Shi; Zongyuan Pan; Fubiao Zhou; Renchao Yin (Engineering Geology, 2026)

Lycii Fructus-derived extracellular vesicles-like particles attenuate sodium iodate-induced retinal injury by transporting bioactive cargo molecules - Pan Huang; Xiao-Bo Zhang; Jia-Qi Li; Guan-Wen He; Ying Chen; Ling-Yun Yang; Zai-Long Chi (Chemical Engineering Journal, 2026)

Magnetic droplet carrier robot integrated with AI-fueled on-site detection - Long Jiao; Wentao Yan; Yanjun Hu; Dongliang Li; Zhenting Xie; Zibing Pan; Qianqian Guo; Xiao Yan; Xiang Wu; Qi Wu (Chemical Engineering Journal, 2026)

Assessment of the Immunological Effects of DNA Vaccines Carrying Antigen Genes for OVA , OMP and OVA ‐ OMP Against Aeromonas hydrophila and Aeromonas caviae Infections in Sinocyclocheilus grahami and Oreochromis niloticus - Long Zhu; Guowen Zhang; Haitao Gao; Jun Chen; Shouyou Bai; Weibin Li; Zhiqiang Feng; Jinrong Li; Lincong Yuan; Xiaofu Pan; Wenhui Li (Journal of Fish Diseases, 2026)
Aeromonas hydrophila and Aeromonas caviae are two economically significant pathogenic bacteria in aquaculture and are the main causes of bacterial septicemia in fish. Controlling disease caused by these two bacterial pathogens is becoming a greater challenge due to increases in the antibiotic resistance of bacteria. Here, we developed and applied novel DNA vaccines carrying antigen genes for ovalbumin (OVA) and the outer membrane protein (OMP) of A. hydrophila to evaluate their immunoprotective effects against these two Aeromonas species and promote the green development of the aquaculture industry. Sinocyclocheilus grahami ( S. grahami ) and Oreochromis niloticus ( O. niloticus ) were subjected to oral vaccination treatment for a total of 21 days. Seven days after being injected with 100 μL of 1 × 10 9 CFU/mL of A. hydrophila or A. caviae , significant decreases were observed in the following non‐specific immune indicators: superoxide dismutase (SOD), complement C3 (C3), lysozyme (LZM) and immunoglobulin M (IgM). However, levels of SOD, C3, LZM and IgM remained stable in fish serum following administration of the OVA, OMP and OVA‐OMP vaccines. Histopathological analysis indicated that oral vaccination with the OVA vaccine could alleviate the splenic lesions caused by A. hydrophila and A. caviae in S. grahami . After challenge with A. hydrophila , the immune protection rates of the OVA, OMP and OVA‐OMP vaccines in S. grahami were 92.56%, 88.89% and 73.33%, respectively, and the relative percent survival (RPS) of O. niloticus was 75%, 83.38% and 50%, respectively. Following challenge with A. caviae , the RPS values for S. grahami vaccinated with the OVA, OMP and OVA‐OMP vaccines were 100%, 86.96% and 95.70%, respectively, and the RPS values for O. niloticus were 92.27%, 96.19% and 92.27%, respectively. In conclusion, oral administration of the OVA, OMP and OVA‐OMP DNA vaccines significantly enhanced both non‐specific and specific immune responses, providing strong protection against A. hydrophila and A. caviae infections in S. grahami and O. niloticus . Future work should focus on optimizing vaccine stability (e.g., improving the OVA‐OMP fusion construct), expanding coverage to other economically important and endangered fish species and clarifying long‐term immune memory mechanisms to support sustainable aquaculture development.

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Suicide attempt risk among patients receiving methylphenidate: a retrospective cohort study - Tai-Long Pan; Li-Chi Chen; Ju-Wei Hsu; Ya-Mei Bai; Shih-Jen Tsai; Tzeng-Ji Chen; Mu-Hong Chen (Psychopharmacology, 2026)
Background Methylphenidate may reduce suicide risk among patients with attention-deficit hyperactivity disorder. Several studies have noted that the association between methylphenidate use and suicidality is weakening. Methods Data were collected from Taiwan’s National Health Insurance Research Database to assess the association between methylphenidate exposure and suicide attempt risk across two exposure periods (main analysis: 2001–2002; duplication analysis: 2004–2005). We compared suicide attempt risk between patients who initiated methylphenidate treatment and those with no recorded psychiatric treatment or methylphenidate exposure during the same period. Results In both the main and duplication analyses, patients receiving methylphenidate exhibited a higher subsequent risk of suicide attempts than unexposed individuals. A duration–response pattern was observed in both cohorts: the hazard ratio of suicide attempts declined with longer cumulative methylphenidate use, from 1.60/1.84 for < 30 days to 1.45/1.65 for ≥ 180 days. Because hazard ratios were closely aligned across 2001–2002 and 2004–2005, the association of methylphenidate with reduced suicide attempt risk did not appear to decrease over time. Discussion Longer use of methylphenidate was associated with a lower risk of subsequent suicide attempts among patients in Taiwan receiving methylphenidate. The beneficial effect of methylphenidate on suicide risk remained consistent over time.

Stress Interference between Multi-radial Boreholes During Hydraulic Fracturing in Multilayered Reservoirs Based on the Discrete Lattice Method - Tengda Long; Xiaoguang Wu; Yazhou Shen; Zixiao Xie; Zhongwei Huang; Gensheng Li; Rui Yang; Zhaowei Sun; Tao Pan; Naikun Hu; Xiaohua Wang (Rock Mechanics and Rock Engineering, 2026)

A comparison of in-situ and ex-situ phosphonate HEDP removal from industrial reverse osmosis concentrate by Fe(II)/calcium peroxide process: Implications for total phosphorus (TP) management - Jin Xia; Yi Wang; Xiaochang Huang; Xiang Li; Xuejun Long; Jun Wan; Jiaqi Ding; Fei Pan (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insight into the “intermediate effect”: Competitive adsorption and surface coverage model in controlling hydrate formation in a closed-cell foam–SDS system - Yi-Feng Wang; Zhen-Guo Qi; Zhen Pan; Li-Yan Shang; Zhi-Ming Liu; Jie Liu; Zhuo-Fan Ma; Long-Qi Meng (Chemical Engineering Journal, 2026)

Fermented wheat germ attenuates metabolic dysregulation in offspring induced by maternal high-fat diet: insights from multi-omics analyses - Xiaolin Li; Yingyu Zhao; Aimei Liao; Long Pan; Yurong Xing; Jingjing Cheng; Jin Liu; Jihong Huang (Food Bioscience, 2026)

Molecular switch engineering manipulates Zn ion transfer enabling fast charging Zn-ion batteries - Yuying Li; Qing Xin; Pan Feng; Junnan Qu; Jingxuan Ren; Jiahao Lei; Jinhao Chen; Jingyao Li; Renming Liu; Xintao Long; Xinli Guo; Dan Luo; et al. (Chemical Engineering Journal, 2026)

Assessing NEX-GDDP-CMIP6 for extreme-temperature simulation in Northwest China and projecting changes under SSP-based scenarios - Qian Li; Tongfei Zhang; Shuang Wang; Xiaohua Fu; Long Cheng; Pan Wang; Juan Feng (Climate Dynamics, 2026)

Realization of elastic Weyl semimetal phases with skyrmion spin textures - Yuang Pan; Liang Si; Miao Yang; Ning Han; Li Zhang; Qiaolu Chen; Rui Zhao; Fujia Chen; Yudong Ren; Wenhao Li; Yuze Hu; Mingyu Tong; et al. (Science Bulletin, 2026)

Life cycle assessment and multi-objective optimization of CO₂ capture via organic amine-based chemical absorption - Hongjuan Zhang; Yangyang Cao; Yunbing Ma; Yibo Pan; Jingying Li; Long Xu; Xiaoxun Ma (Journal of Environmental Chemical Engineering, 2026)

Upcycling anaerobic digestion methane to single-cell protein as a low-carbon strategy - Pan-Long Lv; Qing-Rui Hu; Yu-Yang Hu; Wenjing Gong; Qian Li; Rong Chen (Resources, Conservation and Recycling, 2026)

Wolframite and cassiterite geochemistry deciphers W–Sn ore formation: A case study from the Zuoba quartz-vein tungsten deposit, South China - Kai-Han Zhang; Jun-Yi Pan; Pei Ni; Gen-Wen He; Lin-Lin Peng; Ming-Sen Fan; Yuan-Long Zhang; Wen-Sheng Li (Journal of Asian Earth Sciences, 2026)

A novel phage and its protective effects against Hafnia paralvei in Cyprinus carpio Koi - Lingting Pan; Chenxin Qu; Wencai Liu; Long Tan; Xiaoying Jing; Jinpeng Xu; Wei Lin; Dengfeng Li; Yigang Tong (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Evolution of the westerlies and the East Asian winter monsoon during the late Miocene and Pliocene - Yan Zhao; Long Ma; Kang-Jun Huang; Yuanqiang Guo; Feng Pan; Ruiming Chen; Jianxing Li; Qi Wang; Jianan Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Human activities and horizontal gene transfer shape the resistome landscapes of non-human primates - Yue Sun; Mingyi Zhang; Yang Teng; Yueqi Yin; Jingcheng Ran; Haijun Su; Hongjia Li; Xiaolong Huang; Zexu Long; Xue Sun; Huijuan Pan; Xiaochen Wang; et al. (Journal of Hazardous Materials, 2026)

Discovery of ActRIIB antagonistic peptides from in vitro-digested chicken breast meat via an integrated Peptidomics and molecular docking approach - Fei Zhao; Junwei Yan; Zhiguo Liu; Daodong Pan; Yanli Wang; Long Li; Shikun Suo; Kuo Dang; Dongbing Li; Yali Dang; Xinching Gao (Food Research International, 2026)

The multi-carboxyl metal-organic framework MIL-101(Fe) effectively adsorbs total purines from whole soybean seeds - Deshuai Shao; Cui He; Na Li; Yuqing Gao; Xiaoyu Hu; Yingrun Cai; Qinqin Zhang; Jiahui Yao; Shuo Wang; Yifan Yang; Jiayi Pan; Huihui Gao; et al. (Food Chemistry, 2026)

Associations of paraben exposures measured by repeated urinary biomarkers with sperm DNA damage and apoptosis - Xiu-Ting Li; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Ning Zhang; Long Ge; Han-Qin Ye; Pan-Pan Chen; et al. (Environmental Research, 2026)

Effects of low-temperature storage on the physiology, biochemistry, and predation ability of Eocanthecona furcellata (Wolff) (Hemiptera: Pentatomidae) - Ling-Yi Liu; Chun-Ni Pan; Meng-Shuang Yao; Wei-Zhou; Zhi-Li Li; Hao-Jun Li; Wen-Long Chen (Phytoparasitica, 2026)

Incomplete lineage sorting, hybridization and polyploidization blurred phylogenetic relationships of gentians from the Qinghai-Tibetan Plateau - Shan-Shan Sun; Shu-Han Xu; Wen-Jie Yi; Shi-Long Chen; Pan Li; Daiki Takahashi; Harue Abe; Xiao-Lei Ma; Peng-Cheng Fu (Molecular Phylogenetics and Evolution, 2026)

A novel ambient-mesophilic two-phase anaerobic digestion system enhances methane production and process stability of food waste leachate under ammonia stress - Zunjing Lv; Tingting Zhang; Xiaofang Pan; Zhi-Long Ye; Donghua Xie; Guanjing Cai; Quan-Bao Zhao; Yanlin Li (Chemical Engineering Journal, 2026)

Effect of histone acetylation on plant resistance to salt stress - Tingyue Yang; Zesheng Liu; Xuejuan Pan; Wenying Wei; Caiting An; Long Li; Yuanhui Wang; Weibiao Liao; Chunlei Wang (Plant and Soil, 2026)

Performance of heavy metals in the intertidal zone surface sediments of the Yellow River Estuary under water-sediment regulation scheme - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Ma; Feng Min Pan; Jian Wei Xing; Chen Long Feng; De Tong Tian; Zhi Bo Wang; Rui Wang (Marine Pollution Bulletin, 2025)

Corrigendum to “Electrodialysis, a promising approach for nutrients recovery from anaerobic liquid digestate: Status, challenges and perspectives” [J. Water Process Eng. 72 (2025) 107658] - Xiaofang Pan; Yenan Li; Yahui Huang; Jingwei Xu; Chenyue Sun; Zhi-Long Ye (Journal of Water Process Engineering, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

Corrigendum to “Effects of thermostable α-amylase and autoclave treatment-debranching on starch–lauric acid complex structure, digestibility, and thermal properties” [Food Chem. 480 (2025) 143821] - Yinchen Hou; Chuanyi Hui; Chenyu Li; Zhen Wang; Qihui Shi; Long Pan; Mingqian Gao; Mingyi Zhang; Jihong Huang (Food Chemistry, 2025)

Wheat germ peptides enhance hypoxia tolerance by modulating gut microbiota and reprogramming brain energy metabolism in mice - Jing-yang Cai; Ying-Ying Liu; Meng-Cheng Li; Xin-Xin Guo; Ai-Mei Liao; Yin-Chen Hou; Quan-Ping Liu; Yong-Chao Fan; Long Pan; Ji-Hong Huang (Food Bioscience, 2025)

Radial borehole fracturing in the multilayered shale oil reservoir based on a 3D discrete lattice model - Zixiao Xie; Tengda Long; Xiaoguang Wu; Zhongwei Huang; Gensheng Li; Xianzhi Song; Rui Yang; Tao Pan; Wenchao Zou; Zhaowei Sun; Yaoyao Sun; Naikun Hu; et al. (Engineering Geology, 2025)

Development and performance evaluation of an anoxic-aerobic combined treatment system packed with carbonate rocks for acid mine drainage - Qiang Li; Ruixue Zhang; Jipei Ao; Pan Wu; Xiaoting Long; Chuan Luo (Journal of Water Process Engineering, 2025)

Insight into the carapace discoloration of black tiger shrimp (Penaeus monodon) during frozen storage from the perspective of protein - Chuang Pan; Jingrong Ma; Yuan Chai; Xiaoshan Long; Jianwei Cen; Chunsheng Li; Yongqiang Zhao (Food Chemistry, 2025)

Preparation of high-specificity monoclonal antibody based on rational hapten design and development of immunoassay for accurate detection of dexamethasone in milk and animal tissues - Hongfei Yang; Liangni Qin; Jiaxu Xiao; Xiaoming Pan; Shiyun Han; Linwei Zhang; Jixiang Liang; Yu Si; Hao Wen; Long Li; Xingyu Wang; Xiaojuan Zhang; et al. (Food Bioscience, 2025)

Spin orbit charge transfer enhances intermolecular hydrogen atom transfer catalyzed polymerization for conductive elastomers syntheses - Qingze Pan; Saran Long; Jianwei Li; Pengzhong Chen; Junhui Wang; Kaifeng Wu; Jiangli Fan; Xiaojun Peng (Chemical Engineering Journal, 2025)

Localized surface plasmon enhancement strategy with synergistic dual-mechanism fluorescence quenching for developing highly sensitive lateral flow immunoassays - Mingyue Ding; Hao Wen; Long Li; Yu Si; Jixiang Liang; Shixiang Wu; Linwei Zhang; Hongfei Yang; Shiyun Han; Xiaoming Pan; Yiting Wang; Jiacan Wang; et al. (Chemical Engineering Journal, 2025)

Impact of sodium intake on blood pressure, mortality and major cardiovascular events: an umbrella review of systematic reviews and meta-analyses - Qiuyu Yang; Robin W. M. Vernooij; Hongfei Zhu; Gihad Nesrallah; Chunyang Bai; Qi Wang; Ying Li; Danni Xia; Małgorzata M. Bała; Sylwia Warzecha; Mingyao Sun; Ahmad Jayedi; et al. (Critical Reviews in Food Science and Nutrition, 2025)

On the hotspot-Sun angular offset in urban thermal anisotropy - Wenfeng Zhan; Lu Jiang; Guanwen Chen; Jian Hang; Pan Dong; Shasha Wang; Long Li; Huilin Du (Remote Sensing of Environment, 2025)

Bridging missing GNSS phase measurements through cycle slip detection for improved smartphone positioning - Jiahuan Hu; Wu Chen; Pan Li; Xiaolong Mi; Kai Zheng; Long Tang; Wanke Liu; Jingkai Yuan; Sunil Bisnath (Journal of Geodesy, 2025)

Assessing urban emergency medical services accessibility for older adults considering ambulance trafficability using a deep learning approach - Zhuo Liu; Enjia Zhang; Shuo Pan; Sichun Li; Ying Long; Frank Witlox (Sustainable Cities and Society, 2025)

Prediction of next-day 1-km canopy urban heat island by integrating a multi-block convolutional neural network with satellite- and ground-based observations - Shuang Ge; Wenfeng Zhan; Jiufeng Li; Long Li; Pan Dong; Xiang Li; Chenguang Wang; Chunli Wang; Yihan Gao (Sustainable Cities and Society, 2025)

Chemotactic response during acidogenic fermentation: The key for microorganisms to resist the stress of phthalic acid esters - Yi Zheng; Yanran Zhang; Xinyu Peng; Su Chang; Pan Wang; Bolin Zhu; Guoying Wang; Long D. Nghiem; M.A.H. Johir; Yuquan Wei; Ji Li; Xiaoping Wang (Chemical Engineering Journal, 2025)

Chitosan/PEO@Eu-MOF nanofiber membrane-based test strip for visual detection of tetracycline with smartphone-assisted analysis - Wei Pan; Zi-Han Zhu; Yan-Shen Zhao; Jie-Liu; Zhi-Guang Zhang; Gui-Xia Li; Tao Yu; Zhong-Zhi Han; Yun-Ze Long; Gui-Feng Yu (Chemical Engineering Journal, 2025)

Phosphoric waste acid meets iron-rich tailings: A closed-loop route to FePO4 - Hailin Long; Xianqing Xu; Siwei Li; Deqing Zhu; Jian Pan; Zhengqi Guo (Journal of Water Process Engineering, 2025)

Quantitative Reconstruction of Salinity and Precipitation Changes in Central Asia over the Past 3 200 Years Using Diatom and Pollen Records of Lacustrine Sediment in Aibi Lake of SW Junggar Basin - Long Pan; Guoqiang Li; Xiaoyan Wang; Ming Jin; Xinrong He; Luo Qin; Zhong Wang; Wenwei Zhao; Chunzhu Chen; Yuanlu Liu; Jin Yang; Lele Shu (Journal of Earth Science, 2025)

Effects of thermostable α-amylase and autoclave treatment-debranching on starch–lauric acid complex structure, digestibility, and thermal properties - Yinchen Hou; Chuanyin Hui; Chenyu Li; Zhen Wang; Qihui Shi; Long Pan; Mingqian Gao; Mingyi Zhang; Jihong Huang (Food Chemistry, 2025)

Shifts in soil prokaryotic community structure due to clear-cutting secondary Acacia mangium forests and replacing with Eucalyptus urophylla - Yun-Long Zhang; Ning Pan; Wen-Tao Qiao; Richard P. Dick; Dao-Lin Du; Kun Chen; Shan-Shan Qi; Yan Li; Yi Zhou; Yong-Feng Wang (Journal of Environmental Management, 2025)

The microstructural engineering of NiCo2O4 spinel oxides and their catalytic application in methane emission abatement - Cunshuo Li; Shiyi Pan; Wenzhi Li; Nan Zhang; Zhiqin Xu; Jiangtao Hu; Ling Long (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Diffusion of electric vehicles in Beijing considering indirect network effects” [Transport. Res.: Transp. Environ. 127 (2024) 104069] - Lijing Zhu; Wen-Long Shang; Jingzhou Wang; Yixin Li; Chulung Lee; Washington Ochieng; Xunzhang Pan (Transportation Research Part D: Transport and Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Initial products analysis and mechanistic insights into polystyrene pyrolysis via in-situ photoionization mass spectrometry - Yunqing Zhou; Shi Feng; Hualiang Li; Long Zhao; Zeyou Pan; Zhenzhen Wu; Chuanqi Shi; Zongao Zhen; Zhongyue Zhou; Hao Zhang; Jianhua Yan (Chemical Engineering Journal, 2025)

Simulating the influence of the lake on an extreme precipitation process in the mid-latitude East Asian monsoon fringe region: a case of Chagan Nur Lake - Yue Jing; Long Pan; Ningning Zhang; Yun Shen; Yingqiang Shi; Dandi Liang; Qian Li (Climate Dynamics, 2025)

Estimation of SOC using VNIR and MIR hyperspectral data based on spectral-to-image transforming and multi-channel CNN - Aohua Tang; Guijun Yang; Zhenhong Li; Yuchun Pan; Yu Liu; Huiling Long; Weinan Chen; Jing Zhang; Yue Yang; Xiaodong Yang; Bo Xu (Computers and Electronics in Agriculture, 2025)

FNDC5 alleviates Ox-LDL-induced HUVECs dysfunction by inhibiting ferroptosis through AMPK/Nrf2 signaling - Yipeng Du; Hong Ouyang; Huiyong Wang; Jian Shi; Yuanqing Li; Lingling Xu; Caiyun He; Xiudi Pan; Huidong Long (Tissue and Cell, 2025)

Electrodialysis, a promising approach for nutrients recovery from anaerobic liquid digestate: Status, challenges and perspectives - Xiaofang Pan; Yenan Li; Yahui Huang; Jingwei Xu; Chenyue Sun; Zhi-Long Ye (Journal of Water Process Engineering, 2025)

Deep learning-driven reconstruction of PM2.5 vertical profiles: A fusion of lidar and tower data - Zihuai Yi; Yan Xiang; Long Yun; Xi Mu; Zhenyi Chen; Yuanzhu Dong; Feilong Li; Yin Pan; Lihui Lv; Tianshu Zhang; Wenqing Liu (Journal of Cleaner Production, 2025)

Synergistic generation of ROS via covalent organic frameworks with excellent energy transfer and charge transfer characteristics for phenolic pollutants treatment - Long Zhang; Liujun Yang; Wanyu Wei; Shaoshuo Wang; Yicheng Pan; Yuhan Gu; Liren Gu; Chen Yu; Hua Li; Jianmei Lu (Journal of Environmental Chemical Engineering, 2025)

An improved groundwater vulnerability evaluation model based on random forest algorithm and spatio-temporal change prediction method - Bo Li; Pan Wu; Menghua Li; Lixia Chen; Lei Yang; Jie Long (Process Safety and Environmental Protection, 2025)

Effects of reactive oxygen species on fruit ripening and postharvest fruit quality - Wenying Wei; Zesheng Liu; Xuejuan Pan; Tingyue Yang; Caiting An; Yuanhui Wang; Long Li; Weibiao Liao; Chunlei Wang (Plant Science, 2025)

The evolution of sulfur during coalification in marine land interaction environments based on the sequential extraction of different sulfur species - Shuangxue Du; En Long; Yu Qi; Yiwen Ju; Pan Wu; Yong Fu; Shangyi Gu; Hao Zhang; Qingguang Li (Marine and Petroleum Geology, 2025)

Removal of microplastics in sludge during intensive treatment processes in a wastewater treatment plant in China - Huan Li; Wei Pan; Lifen Yao; Lihui An; Long Zhu; Jinhua Gao; Manxiang Wang; Yulin Kang (Journal of Cleaner Production, 2025)

Dynamic effects of ultrasonic treatment on flavor and metabolic pathway of pumpkin juice during storage based on GC–MS and GC-IMS - Manjun Zhang; Chunli Zhou; Wei Su; Renqin Tan; Long Ma; Wenhui Pan; Wen Li (Food Chemistry, 2025)

Untargeted metabolomics reveals biochemical changes in wheat by-products during fermentation - Han Li; Long Pan; Xiaoyu Wu; Aimei Liao; Guanghai Yu; Yinchen Hou; Jihong Huang (Food Bioscience, 2025)

scCrab: A Reference-Guided Cancer Cell Identification Method based on Bayesian Neural Networks - Heyang Hua; Wenxin Long; Yan Pan; Siyu Li; Jianyu Zhou; Haixin Wang; Shengquan Chen (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Improvement of the gel properties of curdlan gel by hydrogen bonding interaction with trehalose - Long-Qing Li; Le-Yi Pan; Tong-Xin Liang; Mingyu Jin; Ya-Hui Yu; Xiangying Yu; Xiaozhen Liu; Fengyuan Liu; Yuting Li; Jing-Kun Yan (Food Hydrocolloids, 2025)

A novel K57-specific Klebsiella pneumoniae phage disinfects milk and inhibits biofilm formation - Sixiang Xu; Xiaona Yan; Pei Li; Xiaoyue Li; Xiangkuan Zheng; Xiaoxiao Pang; Long Chen; Zihao Pan; Jiale Ma; Xiang Huo; Wei Zhang (Food Control, 2025)

A novel strategy for improving ammonia resistance of acidogenesis using domesticated sludge combined with nZVI addition in an ambient anaerobic digestion system - Zunjing Lv; Xiaofang Pan; Zhi-Long Ye; Donghua Xie; Guanjing Cai; Nan Lv; Yanlin Li (Water Research, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Bi2O2Se nanosheets coated with rosmarinic acid for colon-targeted treatment of inflammatory bowel disease - Jiahu Yao; Yang Yang; Hu Zhao; Chuanming Wang; Liang Jin; Tengyun Long; Wei Huang; Xiang Zhan; Xin Li; Xin Chen; Jinhu Xie; Bin Wu; et al. (Chemical Engineering Journal, 2025)

A novel reaction between ammonia and Criegee intermediates can form amines and suppress oligomers from isoprene - Xiaoying Li; Long Jia; Yongfu Xu; Yuepeng Pan (Science of The Total Environment, 2024)

Highly selective separation of 99TcO4−/ReO4− with rapid liquid-liquid two-phase disengagement by amine-diamide ligands - Long Li; Xuanhao Huang; Xiaoyang Hu; Xingyue Liu; Rui Li; Hang Zhou; Fengfeng Li; Fangxiang Luo; Qingjiang Pan; Songdong Ding (Journal of Environmental Chemical Engineering, 2024)

Maternal Serum Iodine Concentrations in Early Pregnancy Exhibited Well Diagnostic Ability for Thyroid Dysfunction, Inverse Associations with Gestational Weight Gain, and Birth Size: Longitudinal Analyses Based on Huizhou Mother-Infant Cohort - Zhao-min Liu; Huan-huan Long; Dan Li; Ai-ping Fang; Chao-gang Chen; Cheng Wang; Min-min Li; Yi Wu; Su-juan Zhang; Wen-jing Pan (Biological Trace Element Research, 2024)

Architecture of the ATP-driven motor for protein import into chloroplasts - Ning Wang; Jiale Xing; Xiaodong Su; Junting Pan; Hui Chen; Lifang Shi; Long Si; Wenqiang Yang; Mei Li (Molecular Plant, 2024)

Microcrystalline-Fe2P4O12 as eco-friendly and efficient anode for high-performance dual-ion battery - Yunbing He; Xuexue Pan; Qingping Long; Hao Yang; Hongkun Huang; Haoxu Zhan; Yiran He; Zhazira Supiyeva; Chao Li; Qamar Abbas (Chemical Engineering Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Potentially toxic element source apportionment and risk assessment in agricultural soils around a large-scale Pb-Zn mine in Southwest China - Heng Wei; Xuekui Niu; Minmin Li; Canwen Cui; Zhonghua Wei; Wei Long; Man Tang; Hong Yu; Peng Zhang; Liping He; Bo Pan (Journal of Environmental Chemical Engineering, 2024)

Determining obstructive or promoting effects of anions and DOM on phosphate transport combining with Donnan dialysis and selective electrodialysis - Yenan Li; Zhi-Long Ye; Natalia Pismenskaya; Xiaofang Pan; Yahui Huang; Semen Mareev; Andrey Gorobchenko (Desalination, 2024)

Impacts of wastewater treatment plant effluents on dissolved inorganic carbon in highly urbanized karst rivers, Southwest China - Guangxi Long; Y. Jun Xu; Xingxing Cao; Pan Wu; Kai Li (Journal of Hydrology, 2024)

Single-grain luminescence dating of Manas Lake paleoshorelines reveals late quaternary glacial meltwater forced lake level highstand in arid Central Asia - Xiaoyan Wang; Guoqiang Li; He Yang; Yixuan Wang; Ming Jin; Zhongfeng Yan; Caixin Qin; Siyi Gou; Long Pan; Jin Yang (Quaternary Geochronology, 2024)

Optimal emission control plan aiming to basically eliminate PM2.5 heavy pollution in North and Northwest China in 2018 - Zhilan Ye; Long Cheng; Jie Li; Fei Pan; Wenyi Yang; Xueshun Chen; Huiyun Du; Tao Wang; Zhe Wang; Zifa Wang (Journal of Cleaner Production, 2024)

Exploring the therapeutic efficacy and pharmacological mechanism of Guizhi Fuling Pill on ischemic stroke: a meta-analysis and network pharmacology analysis - Jing Wang; Xinmin Li; Junzi Long; Qian Gao; Mengyang Pan; Fangjie Yang; Yasu Zhang (Metabolic Brain Disease, 2024)

Late Holocene decoupling of lake and vegetation ecosystem in response to centennial-millennial climatic changes in arid Central Asia: A case study from Aibi Lake of western Junggar Basin - Long Pan; Guoqiang Li; Chunzhu Chen; Yuanlu Liu; Ji Lai; Jin Yang; Ming Jin; Zhong Wang; Xiaoyan Wang; Weiping Ding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Soil organic carbon storage, microbial abundance and pore structure characteristics of macroaggregates across a soil-landscape sequence in a subtropical hilly watershed - Zheng Zhao; Xiao Feng; Chun Liu; Yue Han; Guogang Long; Shuotong Chen; Qingmei Lin; Jingwen Gong; Yi Shen; Ziyi Mao; Thammavongsa Sounilan; Xuhui Zhang; et al. (CATENA, 2024)

Combining genome-wide association study and linkage mapping in the genetic dissection of amylose content in maize (Zea mays L.) - Wei Dai; Qinglin Li; Tao Liu; Ping Long; Yao He; Mengxiang Sang; Chaoying Zou; Zhong Chen; Guangsheng Yuan; Langlang Ma; Guangtang Pan; Yaou Shen (Theoretical and Applied Genetics, 2024)

Exploring the Impact of Biodegradable and Nonbiodegradable Microplastic Particles on Pb Absorption in Maize - Dan QIU; Chunmiao LU; Huarong SUN; Chaohang LI; Guangqiang LONG; Ping ZHAO; Yijun LONG; Yue DING; Cuixia SU; Zhengyan PAN; Yuefang CAO; Shuran HE (Journal of Soils and Sediments, 2024)

Adaptation of a prey population to increasing predation risks - Ling Pan; Han Zhu; Yan Wang; Bao-Chun Shi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen; Yi-Long Xi (Hydrobiologia, 2024)

Effects of equatorial plasma bubble-induced ionospheric gradients on GNSS PPP-RTK - Long Tang; Fenkai Zhang; Pan Li; Yuanfan Deng; Wu Chen (GPS Solutions, 2024)
Equatorial plasma bubble (EPB) exerts a severe threat to global navigation satellite system (GNSS) technique. It not only can lead to ionospheric scintillation, but also can create strong plasma gradients in ionosphere. In this study, we investigate the effects of EPB-induced ionospheric gradients on GNSS precise point positioning with real-time kinematic (PPP-RTK) technique for the first time. A common medium-scale EPB event occurred in ionosphere over the southern U.S. on May 28, 2017 is served as a case. The results show, during the period of the EPB event, the interpolated ionospheric residuals are very large with maximum 7.5 TECU without EPB correction while the counterparts are generally below 1 TECU with EPB correction. As for the 3D positions, EPB-induced ionospheric gradients mainly affect the initialization or re-initialization process of PPP-RTK solutions, which significantly increase the estimated errors and lengthen the convergence times. This study can help the GNSS community understand EPB’s impacts on GNSS PPP-RTK more deeply and provide support for its mitigation in the next work.

Shock-endurable and reversible evolution between CoOOH and intermediate governed by interfacial strain for fluctuating oxygen evolution - Hongxia Yin; Lihua Qian; Hengbo Xiao; Long Zhang; Ximin Li; Xiangji Zhou; Songliu Yuan; Canglong Li; Qiuhong Lu; Fei Pan; Liqing Zeng; Junjie Guo; et al. (Chemical Engineering Journal, 2024)

Sugarcane borers: species, distribution, damage and management options - Ao-Mei Li; Zhong-Liang Chen; Fen Liao; Yong Zhao; Cui-Xian Qin; Miao Wang; You-Qiang Pan; Shao-Long Wei; Dong-Liang Huang (Journal of Pest Science, 2024)
Lepidopteran borers stand out as the most destructive pests in sugarcane, leading to reductions in stalk weight, juice quality and sugar recovery. Presently, integrated pest management (IPM) systems are utilized for sugarcane borer management, employing diverse methods encompassing cropping system, chemical pesticides, behavioral manipulation, biological agents and the selection of resistant varieties. However, the effectiveness of this strategy remains controversial due to concerns about harmful residues, formulation limitations, environmental variability, labor shortages and increased input costs. Currently, multiple lines of transgenic sugarcane expressing insecticidal genes from the bacterium Bacillus thuringiensis (Bt) have been developed globally, offering the prospect of increases production with reduced pesticides application, thereby eliminating the negative effect of IPM. In Brazil, the first genetically modified sugarcane cultivars resistant to the sugarcane borer have been approved and released for commercial cultivation, shedding a bright light on a viable solution for sugarcane borers. This paper reviews borer species and distribution, the significant damage caused by sugarcane borers, current control approaches and the future effective control strategies. Additionally, this work provides comprehensive understanding on Bt sugarcane, serving as an additional tool to complement conventional sugarcane borers control resistance programs.

Evaluation of Opaque-2 effects on popping characteristics using iTRAQ-based proteome profiles in popcorn - Yongbin Dong; Qi Zheng; Junjie Zhu; Qingling Shi; Siqi Jiang; Mengying Pan; Xinyue Zhang; Long Zhang; Yuling Li (Euphytica, 2024)

Reference Intervals of Serum Iodine Concentration in Chinese Pregnant Women - Yi Wu; Huan-huan Long; Su-juan Zhang; Min-Min Li; Chao-gang Chen; Cheng Wang; Zheng-yu Sheng; Yan-bin Ye; Shu-yu Zuo; Wen-jing Pan; Zhao-min Liu (Biological Trace Element Research, 2024)

DNAL7, a new allele of NAL11, has major pleiotropic effects on rice architecture - Jie Wang; Weixiong Long; Jintao Pan; Xiaolin Zhang; Lihua Luo; Mingjuan Qian; Wei Chen; Laiyang Luo; Weibiao Xu; Yonghui Li; Yaohui Cai; Hongwei Xie (Planta, 2024)

Social parasitism behavior between two species of edible wasps in China - Cheng-Ye Wang; Hao-Yu Chen; Bing-Qing Fang; Pan-Li Yang; Zhao He; Long Sun; Jin Gan; Min Zhao; Ying Feng (Journal of Ethology, 2024)

Opportunities and challenges of polyphenols and polysaccharides for type 1 diabetes intervention - Binbin Li; Li-Long Pan; Xiaohua Pan; Xiaoliang Dong; Zhengnan Ren; Hao Zhang; Wei Chen; Paul de Vos; Jia Sun (Critical Reviews in Food Science and Nutrition, 2024)

Effects of climate and geochemical properties on the chemical forms of soil Cd, Pb and Cr along a more than 4000 km transect - Zhiqiang Bai; Ting Li; Shirong Zhang; Guiyin Wang; Xiaoxun Xu; Wei Zhou; Xiaomei Pan; Yulin Pu; Yongxia Jia; Zhanbiao Yang; Lulu Long (Journal of Hazardous Materials, 2024)

A critical review on metallurgical recovery of iron from iron ore tailings - Hailin Long; Deqing Zhu; Jian Pan; Siwei Li; CongCong Yang; Zhengqi Guo; Xianqing Xu (Journal of Environmental Chemical Engineering, 2024)

The effect of triclosan on intergeneric horizontal transmission of plasmid-mediated tigecycline resistance gene tet(X4) from Citrobacter freundii isolated from grass carp gut - Xinxin Jiang; Jingfei Long; Yanzhen Song; Xiaoyu Qi; Ping Li; Kuiquan Pan; Chenyang Yan; Hongzhou Xu; Haixia Liu (Environmental Pollution, 2024)

Contrasting moist heat across local climate zones in heat and non-heat waves: Insights from 29 Chinese metropolises - Sida Jiang; Wenfeng Zhan; Long Li; Chunli Wang; Pan Dong; Shasha Wang; Yingying Ji; Fan Huang; Zihan Liu; Yihan Gao (Building and Environment, 2024)

Monospecific and ultrasensitive detection of ofloxacin: A computational chemistry-assisted hapten screening strategy and analysis of molecular recognition mechanism - Jiaxu Xiao; Liangni Qin; Dan Zhao; Niexie Huang; Wennuo Xu; Linwei Zhang; Xiaoming Pan; Shiyun Han; Mingyue Ding; Long Li; Tao Le; Dapeng Peng (Journal of Hazardous Materials, 2024)

Sulfide compositions of young Chang’e-5 basalts and implications for sulfur isotopes in lunar basalt sources - Zaicong Wang; Yiheng Li; Wen Zhang; Qi He; Fabin Pan; Zhaochu Hu; Keqing Zong; Yantong Feng; Harry Becker; James M.D. Day; Wenlei Song; Hejiu Hui; et al. (Geochimica et Cosmochimica Acta, 2024)

Highly efficient solution-processable four-coordinate boron compound: A thermally activated delayed fluorescence emitter with short-lived phosphorescence for OLEDs with small efficiency roll-off - Zhengqin Pan; Jie Pan; Long Sang; Zhenming Ding; Meihua Liu; Laichao Fu; Mengqiu Wang; Xiaokang Huang; Bowen Li; Shaofeng Chen; Dongcheng Chen; Yu Liu; et al. (Chemical Engineering Journal, 2024)

Diffusion of electric vehicles in Beijing considering indirect network effects - Lijing Zhu; Wen-Long Shang; Jingzhou Wang; Yixin Li; Chulung Lee; Washington Ochieng; Xunzhang Pan (Transportation Research Part D: Transport and Environment, 2024)

Revolutionizing sanitation: Valorizing fecal slags through co-digesting food waste at high-solid content and dosing metallic nanomaterials for anaerobic digestion stability - Hamza Hassan Yusuf; Xiaofang Pan; Zhi-Long Ye; Guanjing Cai; Lise Appels; Jiasheng Cai; Zunjing Lv; Yanlin Li; Jing Ning (Journal of Environmental Management, 2024)

UHPLC-QTOF-MS-based untargeted metabolomic authentication of Chinese red wines according to their grape varieties - Xiao-Li Yin; Zhi-Xin Peng; Yuan Pan; Yi Lv; Wanjun Long; Hui-Wen Gu; Haiyan Fu; Yuanbin She (Food Research International, 2024)

Removal of toxic metals using iron sulfide particles: A brief overview of modifications and mechanisms - Vaishali Sharma; Ruixin Yan; Xiuping Feng; Junqing Xu; Meitian Pan; Long Kong; Liang Li (Chemosphere, 2024)

Identification of inducible CYP3 and CYP4 genes associated with abamectin tolerance in the fat body and Malpighian tubules of Spodoptera litura - Lin Liang; Jianyi Li; Long Jin; Kunpeng Yan; Yiou Pan; Qingli Shang (Pesticide Biochemistry and Physiology, 2024)

Dietary shifts drive the slowdown of declining methylmercury related health risk in China - Yumeng Li; Qiumeng Zhong; Pan He; Long Chen; Haifeng Zhou; Xiaohui Wu; Sai Liang (Environmental Pollution, 2024)

Online and in-situ monitoring of the growth of silver nanowires and nanoparticles with conductive measurement - Huangqing Ye; Xuchao Jian; Ying Wang; Jun Long; Xiaofang Zhang; Junqin Wu; Yingying Pan; Yu Wang; Xiping Zeng; Xian-Zhu Fu; Jing-Li Luo (Chemical Engineering Journal, 2024)

Potentiation of the lateral habenula-ventral tegmental area pathway underlines the susceptibility to depression in mice with chronic pain - Chun-Kui Zhang; Pan Wang; Yuan-Yuan Ji; Jian-Shuai Zhao; Jun-Xiang Gu; Xian-Xia Yan; Hong-Wei Fan; Ming-Ming Zhang; Yu Qiao; Xiao-Die Liu; Bao-Juan Li; Ming-Hui Wang; et al. (Science China Life Sciences, 2024)

Micro-interaction of montmorillonite-loaded nanoparticles with mucin promotes retention of betaxolol hydrochloride on the ocular surface and the tear film microenvironment - Yingshan Zhao; Jie Hu; Yuancheng Ke; Qinqiang Long; Jinlan Mao; Huihui Li; Zhenping Xiao; Kangyiran Pan; Siying Yuan; Jiayi Xue; Wei Li; Meiju Zhong; et al. (Applied Clay Science, 2024)

Therapeutic efficacy and pharmacological mechanism of Yindan Xinnaotong soft capsule on acute ischemic stroke: a meta-analysis and network pharmacology analysis - Fangjie Yang; Xinmin Li; Junzi Long; Qian Gao; Mengyang Pan; Jing Wang; Yasu Zhang (Metabolic Brain Disease, 2023)

White rice consumption and risk of cardiometabolic and cancer outcomes: A systematic review and dose-response meta-analysis of prospective cohort studies - Honghao Lai; Mingyao Sun; Yafei Liu; Hongfei Zhu; Mengting Li; Bei Pan; Qi Wang; Qiuyu Yang; Xiao Cao; Chen Tian; Yao Lu; Xuping Song; et al. (Critical Reviews in Food Science and Nutrition, 2023)

How accompanying ions affect soil heavy metal removal by polyepoxysuccinic acid during washing? - Qinmei Zhong; Shirong Zhang; Ting Li; Guoshu Gong; Xiaoxun Xu; Guiyin Wang; Xiaomei Pan; Wei Zhou; Yulin Pu; Lulu Long; Shengtao Yang; Yue Yuan (Chemosphere, 2023)

Transport of pollutants in groundwater of domestic waste landfills in karst regions and its engineering control technologies - Bo Li; Teng Li; Pan Wu; Lei Yang; Jie Long; Pu Liu; Tao Li (Journal of Environmental Management, 2023)

Manipulating Li2O2 deposition morphology by surface spin modulation of cobalt-based spinel oxide catalysts in lithium−oxygen batteries - Yu Pan; Kun Li; Anjun Hu; Chuan Zhao; Yiming Zhang; Xiaoping Jiang; Baihai Li; Jun Wang; Jianping Long (Chemical Engineering Journal, 2023)

Exploration of the Catalytic Cycle Dynamics of Vigna Radiata H+–Translocating Pyrophosphatases Through Hydrogen–Deuterium Exchange Mass Spectrometry - Li-Kun Huang; Yi-Cyuan Huang; Pin-Chuan Chen; Ching-Hung Lee; Shih-Ming Lin; Yuan-Hao Howard Hsu; Rong-Long Pan (The Journal of Membrane Biology, 2023)

Genetic spectrums and clinical profiles of critically ill neonates with congenital auricular deformity in the China Neonatal Genomes Project - Feifan Xiao; Bingbing Wu; Chenbin Dong; Guoqiang Cheng; Yun Cao; Laishuan Wang; Xinran Dong; Yulan Lu; Lin Yang; Liping Chen; Long Li; Xinnian Pan; et al. (Human Genetics, 2023)

Clinical comprehensive evaluation of direct oral anticoagulants for patients with atrial fibrillation in China - Chi Zhang; Zhi-Chun Gu; Er-Li Ma; Bing-Long Liu; Mang-Mang Pan; Jia Wang; Xin Wang; Bin Wu; Hou-Wen Lin (European Journal of Clinical Pharmacology, 2023)

Simple yet efficient downscaling of land surface temperatures by suitably integrating kernel- and fusion-based methods - Pan Dong; Wenfeng Zhan; Chenguang Wang; Sida Jiang; Huilin Du; Zihan Liu; Yangyi Chen; Long Li; Shasha Wang; Yingying Ji (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Rapid adaptation of a rotifer prey population to non-consumptive predation pressures - Ling Pan; Han Zhu; Yi-Long Xi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen (Hydrobiologia, 2023)

Bacterial antioxidant mechanism in calcium peroxide aided sludge anaerobic fermentation - Li Liu; Yu Pan; Xiaohan Zhi; Long Chen; Hongtao Zhu (Bioresource Technology, 2023)

An integrative protocol for one-step PCR amplicon library construction and accurate demultiplexing of pooled sequencing data - Jiahao Ni; Jiao Pan; Yaohai Wang; Tianhao Chen; Xinshi Feng; Yichen Li; Tongtong Lin; Michael Lynch; Hongan Long; Weiyi Li (Marine Life Science & Technology, 2023)

Global mapping of urban thermal anisotropy reveals substantial potential biases for remotely sensed urban climates - Huilin Du; Wenfeng Zhan; Zihan Liu; E. Scott Krayenhoff; TC Chakraborty; Lei Zhao; Lu Jiang; Pan Dong; Long Li; Fan Huang; Shasha Wang; Yuyue Xu (Science Bulletin, 2023)

Homoacetogenesis is altering the metabolic pathway of acidogenic microbiome and combating volatile fatty acid accumulation in anaerobic reactors - Zunjing Lv; Xiaofang Pan; Zhi-Long Ye; Irini Angelidaki; Nan Lv; Yanlin Li; Guanjing Cai; Lifeng Lin (Journal of Environmental Chemical Engineering, 2023)

Rockfall feature investigation and kinematic simulation based on nap-of-the-object photogrammetry and GIS spatial modeling - Xude Li; Fu-zhen Liu; Li Zhao; Na Deng; Long Chen; Jing-shen Pan; Guo-qiang Tang (Natural Hazards, 2023)

Spatial distribution, pollution characteristics, and health risks of antibiotic resistance genes in China: a review - Zhixiang Xu; Yue Jia; Bin Huang; Dimeng Zhao; Xin Long; Siyuan Hu; Caiqing Li; Guohua Dao; Bo Chen; Xuejun Pan (Environmental Chemistry Letters, 2023)

Competitive adsorption of binary negatively charged proteins in egg white during foam evolution: From bulk solution to air-water interface - Haobo Jin; Jiajing Pan; Qi Zeng; Zuyue Li; Yongguo Jin; Long Sheng (Food Hydrocolloids, 2023)

Dual improvement in acid and redox properties of the FeO /OAC catalyst via APS oxygen-functionalization: High low-temperature NH3-SCR activity, SO2 and H2O tolerance - Simi Li; Yan Huang; Hong Zhu; Jiaqi Long; Ling Xiao; Pan Li; Lingkui Zhao; Junfeng Zhang (Fuel, 2023)

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

A safe anode-free lithium metal pouch cell enabled by integrating stable quasi-solid electrolytes with oxygen-free cathodes - Chuan Zhao; Yu Pan; Runjing Li; Anjun Hu; Bo Zhou; Miao He; Jiahao Chen; Zhongfu Yan; Yining Fan; Nian Chen; Mengjiao Liu; Jianping Long (Chemical Engineering Journal, 2023)

Rational design of molecular phototheranostic platform for NIR-II fluorescence imaging guided chemodynamic-photothermal combined therapy - Gui-long Wu; Bin Sun; Yuxuan He; Xiaofeng Tan; Qi Pan; Sha Yang; Na Li; Minghui Wang; Peixian Wu; Fen Liu; Hao Xiao; Li Tang; et al. (Chemical Engineering Journal, 2023)

A genome-wide co-expression network analysis revealed ZmNRAMP6-mediated regulatory pathway involved in maize tolerance to lead stress - Peng Liu; Li Jiang; Ping Long; Qinglin Li; Fengxia Hou; Guangsheng Yuan; Zhong Chen; Minyan Zhang; Chaoying Zou; Guangtang Pan; Langlang Ma; Yaou Shen (Theoretical and Applied Genetics, 2023)

Effects of PM2.5 pollution and single nucleotide polymorphisms of neurotrophin signaling pathway genes acting together on schizophrenia relapse - Qinggui Lei; Xiaolan Huang; Tongshun Li; Qingqing Zhong; Qiang Chen; Runde Pan; Jianxiong Long; Li Su (International Archives of Occupational and Environmental Health, 2023)

Rayleigh surface wave inversion based on an improved Archimedes optimization algorithm - Zhen-An Yao; Ren Wang; Fu Yu; Long-Feng Chen; Hong-Xing Li; Xiang-Teng Wang; Pan Wang (Applied Geophysics, 2023)

Preliminary Investigation on Marine Radar Oil Spill Monitoring Method Using YOLO Model - Bo Li; Jin Xu; Xinxiang Pan; Rong Chen; Long Ma; Jianchuan Yin; Zhiqiang Liao; Lilin Chu; Zhiqiang Zhao; Jingjing Lian; Haixia Wang (Journal of Marine Science and Engineering, 2023)
Due to the recent rapid growth of ocean oil development and transportation, the offshore oil spill risk accident probability has increased unevenly. The marine oil spill poses a great threat to the development of coastal cities. Therefore, effective and reliable technologies must be used to monitor oil spills to minimize disaster losses. Based on YOLO deep learning network, an automatic oil spill detection method was proposed. The experimental data preprocessing operations include noise reduction, gray adjustment, and local contrast enhancement. Then, real and synthetically generated marine radar oil spill images were used to make slice samples for training the model in the YOLOv5 network. The detection model can identify the effective oil spill monitoring region. Finally, an adaptive threshold was applied to extract the oil slicks in the effective oil spill monitoring regions. The YOLOv5 detection model generated had the advantage of high efficiency compared with existing methods. The offshore oil spill detection method proposed can support real-time and effective data for routine patrol inspection and accident emergency response.

Anti-neuroinflammatory sesquiterpenoids from Chloranthus henryi - Xue-Jiao Wang; Jun-Li Xin; Sheng-Zhou Yu; Li-Long Pan; Jin-Feng Hu; Juan Xiong (Natural Product Research, 2023)

Deployment optimization of battery swapping stations accounting for taxis’ dynamic energy demand - Tian-yu Zhang; En-jian Yao; Yang Yang; Long Pan; Cui-ping Li; Bin Li; Feng Zhao (Transportation Research Part D: Transport and Environment, 2023)

A quantum algorithm for heat conduction with symmetrization - Shi-Jie Wei; Chao Wei; Peng Lv; Changpeng Shao; Pan Gao; Zengrong Zhou; Keren Li; Tao Xin; Gui-Lu Long (Science Bulletin, 2023)

A 40 % paddy surface soil organic carbon increase after 5-year no-tillage is linked with shifts in soil bacterial composition and functions - Jian-Ying Qi; Xiang-Bin Yao; Jian Lu; Long-Xin He; Jun-Li Cao; Zheng-Rong Kan; Xing Wang; Sheng-Gang Pan; Xiang-Ru Tang (Science of The Total Environment, 2023)

Selective separation of volatile fatty acids, nitrogen and phosphorus from anaerobic acidogenic fermentation via forward osmosis membrane process - Xian-Zheng Zhu; Long-Fei Wang; Xin-Rong Pan; Feng Zhang; Min-Sheng Huang; Wen-Wei Li; Hou-Qi Liu (Chemical Engineering Journal, 2023)

Production of hydrocarbon-rich bio-oil from catalytic pyrolysis of waste cooking oil over nickel monoxide loaded corn cob-derived activated carbon - Peng Li; Bo Niu; Helin Pan; Yayun Zhang; Donghui Long (Journal of Cleaner Production, 2023)

Discrimination of the harvesting season of green tea by alcohol/salt-based aqueous two-phase systems combined with chemometric analysis - Xiao-Hua Zhang; Hui-Na Cui; Jing-Jing Zheng; Xiang-Dong Qing; Kai-Long Yang; Ya-Qian Zhang; Lu-Meng Ren; Le-Yuan Pan; Xiao-Li Yin (Food Research International, 2023)

Comprehensive identification and hydrophobic analysis of key proteins affecting foam capacity and stability during the evolution of egg white foam - Haobo Jin; Yongguo Jin; Jiajing Pan; Sijie Mi; Qi Zeng; Zhe Li; Qi Wang; Yi Sun; Long Sheng (Food Hydrocolloids, 2023)

Tailoring mixed geometrical configurations in amorphous catalysts to activate oxygen electrode reactions of lithium-oxygen batteries - Runjing Li; Anjun Hu; Chuan Zhao; Bo Zhou; Miao He; Yining Fan; Jiahao Chen; Zhongfu Yan; Yu Pan; Jianping Long (Chemical Engineering Journal, 2023)

Retraction Note: LINC00665/miR-9-5p/ATF1 is a novel axis involved in the progression of colorectal cancer - Xuhong Zhao; Wenhao Weng; Yin Long; Weijie Pan; Zhi Li; Fenyong Sun (Human Cell, 2022)

Association of soft drink and 100% fruit juice consumption with all-cause mortality, cardiovascular diseases mortality, and cancer mortality: A systematic review and dose-response meta-analysis of prospective cohort studies - Bei Pan; Long Ge; Honghao Lai; Qi Wang; Qi Wang; Qian Zhang; Min Yin; Sheng Li; Jinhui Tian; Kehu Yang; Jiancheng Wang (Critical Reviews in Food Science and Nutrition, 2022)

Damage and Failure Characteristics and Constitutive Model of Copper-Bearing Skarns Disturbed by Hierarchical Dynamic Loading After Loading And Unloading - Chun Wang; Jia Li; Lu- ping Cheng; Xin-ru Li; Pan-long Zhang; Man-gu Hu (Rock Mechanics and Rock Engineering, 2022)

A novel bio-washing eluent obtained from fermentation of fruit wastes for removal of soil Pb: efficiency, mechanism, and risk assessment - Xiaomei Pan; Shirong Zhang; Ting Li; Guiyin Wang; Xiaoxun Xu; Yun Li; Wei Zhou; Jinsong He; Lulu Long; Ouping Deng; Ling Luo; Guoshu Gong (Environmental Science and Pollution Research, 2022)

Characterization of Fine-Scale Turbulence Generated in a Laboratory Orbital Shaker and Its Influence on Skeletonema costatum - Lin Yu; Yifan Li; Zhongzhi Yao; Long You; Zong-Pei Jiang; Wei Fan; Yiwen Pan (Journal of Marine Science and Engineering, 2022)
Turbulence is one of the ubiquitous aspects of aquatic systems and affects many physical and biological processes. Based on direct velocity measurements and a computational fluid dynamics (CFD) simulation, we characterized the distribution of the turbulent kinetic dissipations rates (ε) in an orbital shaker system within a range of rotation frequencies. CFD was able to estimate the ε distribution in containers accurately, which was confirmed by other two methods and was independent of velocity measurement. The results showed that ε was linearly correlated with the rotational frequencies. Despite the existence of gradients of ε and the fact that a mean circular horizontal flow was formed within the tank, the energy levels of the whole tank varied spatially within an order of magnitude and the ε distributions at different rotational frequencies were similar, suggesting that the ε distribution in the whole tank could be seen as quasi-homogeneous. To investigate the influence of turbulence on algae growth, culture experiments of a typical diatom—Skeletonema costatum were carried out under different turbulence conditions. Our results suggested turbulence mixing promoted nutrient uptake and growth of Skeletonema costatum, which could be attributed to the break of the diffusion-limited resource concentration boundary layer surrounding phytoplankton.

Amelioration of Flesh Quality in Hybrid Grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu) Fed With Oxidized Fish Oil Diet by Supplying Lactobacillus pentosus - Xiaobo Yan; Simiao Pan; Zhihao Li; Xiaohui Dong; Beiping Tan; Shuisheng Long; Tao Li; Xiangxiang Suo; Yuanzhi Yang (Frontiers in Marine Science, 2022)
The objective was to investigate the improvement of the flesh quality and nutritional value of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu ) by Lactobacillus pentosus (BL-15). The two diets were prepared with 9% oxidized fish oil (OFO negative control group) or 9% fresh fish oil (FFO positive control group) as the major lipid source, and the OFO diet were sprayed with L. pentosus at 1.0×10 7 , 1.0×10 8 , 1.0×10 9 CFU/g, respectively. Five kinds of diets were fed to hybrid grouper with initial weight of 21.36 ± 0.03 g for 60 days. The results showed that (1) consumption of OFO diet significantly increased muscle crude lipid, total cholesterol, and total monounsaturated fatty acids contents and significantly decreased muscle C20:5n3, C22:6n3, ∑PUFA levels of grouper ( p < 0.05), whereas the addition of L. pentosus to OFO diet significantly reduced muscle crude lipid, malondialdehyde, reactive oxygen radicals, total cholesterol concentration, increased C20:5n3, C22:6n3, ∑PUFA levels, increased muscle crude protein content, and enhanced muscle hardness, gumminess, and chewiness compared with FFO or OFO group ( p < 0.05). (2) In addition, ingestion of OFO diet significantly increased muscle phenylalanine content and significantly decreased aspartic acid content ( p < 0.05), while the addition of L. pentosus restored aspartic acid to the level not significantly different from that of FFO group ( p > 0.05). The addition of L. pentosus also increased tyrosine, lysine, leucine, phenylalanine, arginine, and alanine content compared to FFO group at the same time ( p < 0.05). (3) Furthermore, the intake of OFO diet would lead to deterioration in muscle flavor quality and increase in noxious odors in grouper, and the addition of L. pentosus can mitigate or rectify these detrimental consequences. In further analysis, consumption of OFO group significantly downregulated the mRNA expression of muscle growth factors and caused serious damage to the muscle antioxidant system ( p < 0.05), which was protected against by the potent antioxidant properties of L. pentosus . We recommend the supplementation level of L. pentosus to be 1.0×10 9 CFU/g under the highly oxidized conditions of the present trial fish oil.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

Magnetic properties of surface sediments from Liuxi River, southern China and their environmental significance - Erqi Zheng; Yang Bai; Mingkun Li; Tingping Ouyang; Fangzhi Zhang; Mingjie Yu; Gang Lei; Zhiyi Pan; Gang Long (Journal of Soils and Sediments, 2022)

Effect of tree form on wheat yield via changing microenvironment in almond–wheat intercropping - Wen Zhang; Hui Xie; Shou-An Han; Min Wang; Ming-Qi Pan; Xu Qiao; Long Li (Agroforestry Systems, 2022)

Clinical and Molecular Features of POLG-Related Sensory Ataxic Neuropathy with Dysarthria and Ophthalmoparesis - Li-Xi Li; Li-Ting Jiang; You-Gui Pan; Xiao-Long Zhang; Li-Zhen Pan; Zhi-Yu Nie; Yu-Hui Chen; Ling-Jing Jin (Journal of Molecular Neuroscience, 2021)

The Effect of Oxidized Fish Oil on the Spleen Index, Antioxidant Activity, Histology and Transcriptome in Juvenile Hybrid Grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatus) - Shuisheng Long; Zhihao Li; Xiaohui Dong; Xiaobo Yan; Hao Liu; Beiping Tan; Shuang Zhang; Simiao Pan; Tao Li; Xiangxiang Suo; Yuanzhi Yang (Frontiers in Marine Science, 2021)
The spleen is an important organ in the immune function of fish, and it is also important for hematogenesis and antibody and granulocyte production. However, the effect of oxidized fish oil on the spleen of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatus ) is unknown. In this study, hybrid groupers were fed with oxidized fish oil and the spleen index, antioxidant ability, histology and transcriptome were investigated. Oxidized fish oil did not affect the spleen index. Levels of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px) and malondialdehyde (MDA) in the spleen were significantly increased as the amount of oxidized fish oil in the diet increased, but the vitamin E concentration was significantly decreased. The morphological organization of the spleen was damaged with increased oxidative stress. And the spleen reacted to oxidative stress by platelet activation, FOXO and notch signaling pathways, which involved amyloid beta precursor protein binding family B member 1 interacting protein (APBB1IP) gene, glucose-6-phosphatase (G6PC) gene, histone acetyltransferase p300 (EP300) gene, insulin gene and notch 2 gene. In conclusion, the oxidized fish oil caused oxidative stress and damaged its structure. Additionally, oxidized fish oil changed the transcription profile of the spleen.

How light affect the magnetotactic behavior and reproduction of ellipsoidal multicellular magnetoglobules? - Xinxin Qian; Yicong Zhao; Claire-Lise Santini; Hongmiao Pan; Tian Xiao; Haitao Chen; Tao Song; Jinhua Li; Francois Alberto; Sophie Brustlein; Long-Fei Wu (Journal of Oceanology and Limnology, 2021)

Efficiency and comprehensive risk assessment of soil Pb and Cd by washing technique with three biodegradable eluents - Qinmei Zhong; Shirong Zhang; Xiaomei Pan; Guiyin Wang; Xiaoxun Xu; Ting Li; Wei Zhou; Yan He; Ling Luo; Yan Liu; Lulu Long (Environmental Science and Pollution Research, 2021)

OSI-027 alleviates rapamycin insensitivity by modulation of mTORC2/AKT/TGF-β1 and mTORC1/4E-BP1 signaling in hyperoxia-induced lung injury infant rats - Li Long; Mulin Liang; Yanling Liu; Pan Wang; Hongxing Dang (Molecular & Cellular Toxicology, 2021)

Subcellular Localization of the D27 Protein in Sugarcane (Saccharum spp. Hybrids) Using an Optimized Protoplast Isolation, Purification, and Transient Gene Expression Protocol - Zhuan-di Wu; Xin Hu; Feng-gang Zan; Yong-bao Pan; David M. Burner; Zheng-ying Luo; Jia-yong Liu; Li-ping Zhao; Li Yao; Yong Zhao; Xin-long Liu; Hong-ming Xia; et al. (Sugar Tech, 2021)

Global patterns in leaf stoichiometry across coastal wetlands - Yu‐Kun Hu; Xu‐Yan Liu; Nian‐Peng He; Xu Pan; Song‐Yuan Long; Wei Li; Man‐Yin Zhang; Li‐Juan Cui (Global Ecology and Biogeography, 2021)
Aim Coastal wetlands provide crucial ecosystem functions and services, such as coastal protection, nutrient retention and C sequestration. Despite the important roles in global C, N and P cycling, the global variation in leaf stoichiometry across coastal wetlands remains unclear. Location Global. Time period 1980–2018. Major taxa studied Vascular plants. Methods By compiling a global dataset of 698 data records in 205 sites, we carried out systematic analyses of the world‐wide trends and their determinants of leaf element contents and ratios of plants across coastal wetlands. Results Leaf N and P contents increased significantly, but C:N, C:P and N:P ratios decreased with increasing latitude in coastal wetlands. The mean annual temperature was the predominant driver of leaf N, P and C:N, whereas soil N:P was a good predictor of leaf C:P and N:P ratios. Furthermore, N increased faster with P in plant leaves of coastal wetlands compared with terrestrial ecosystems. Within coastal wetlands, herb‐dominated salt marshes had a significantly higher leaf P content, lower leaf N:P ratio and lower scaling exponent of leaf N to P than tree‐dominated mangroves. Main conclusions The similar latitudinal patterns of leaf stoichiometry in coastal wetlands compared with terrestrial ecosystems reflected the similar influences of temperature. However, different slopes of leaf P and N:P ratios and N and P scaling relationships between these two ecosystems suggested that different salinity and tidal inundation levels result in different strategies of N and P use in coastal wetland plants. These differences in leaf stoichiometry between ecosystems and between different types of coastal wetlands might need to be emphasized in future biogeochemical modelling owing to their different roles in global nutrient and carbon cycling.

LINC00472 regulates vascular smooth muscle cell migration and proliferation via regulating miR-149-3p - Ran Jing; Wei Pan; Tianyi Long; Zhenyu Li; Chuanchang Li (Environmental Science and Pollution Research, 2021)

Prevalence and outcomes of re-positive nucleic acid tests in discharged COVID-19 patients - Hou-wei Du; Jun-nian Chen; Xiao-bin Pan; Xiao-ling Chen; Yixian-Zhang; Shuang-fang Fang; Xiao-qing Li; Pin-cang Xia; Lei Gao; Hai-long Lin; Li-min Chen; Nan Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

NC10 bacteria promoted methane oxidation coupled to chlorate reduction - Zi-Yan Li; Xin Li; Bin Tan; Pan-Long Lv; He-Ping Zhao (Biodegradation, 2020)

Cellulose-based adsorbents loaded with zero-valent iron for removal of metal ions from contaminated water - Xiaoning Li; Jinyao Zhang; Hongtian Xie; Yuanfeng Pan; Jie Liu; Zhihong Huang; Xiang Long; Huining Xiao (Environmental Science and Pollution Research, 2020)

Assessment of Fresh and Dry Rice Straw for Biogas Potential by Anaerobic Digestion - Qiangqiang Liu; Shiyou Pan; Zhongmin Long; Zhenchong Li; Liqin Du; Yutuo Wei (BioEnergy Research, 2020)

RETRACTED ARTICLE: LINC00665/miR-9-5p/ATF1 is a novel axis involved in the progression of colorectal cancer - Xuhong Zhao; Wenhao Weng; Yin Long; Weijie Pan; Zhi Li; Fenyong Sun (Human Cell, 2020)

Cost-reduction strategies in massive genomics experiments - Haichao Li; Kun Wu; Chenchen Ruan; Jiao Pan; Yujin Wang; Hongan Long (Marine Life Science & Technology, 2019)
Many modern biology studies require deep, whole-genome sequencing of hundreds to thousands of samples. Although per-sample costs have dramatically decreased, the total budget for such massive genome sequencing constitutes a significant barrier for poorly funded labs. The costly lab tools required for genomics experiments further hinder such studies. Here, we share two strategies for extensively reducing the costs of massive genomics experiments, including miniaturization of the NEBNext Ultra II FS DNA Library Prep Kit for Illumina (reducing the per-sample total costs to ~ 1/6 of that charged by service providers) and in-lab 3D model-designing of genomics tools. These strategies not only dramatically release funding pressure for labs, but also provide students with additional training in hands-on genomics and 3D-model-designing skills, demonstrating the high potential for their application in genomics experiments and science education.

Rapid adaptation of Brachionus angularis (Rotifera) to invasion by Brachionus calyciflorus - Yi-Long Xi; Ke-Qiang Huang; Ling Pan; Han Zhu; Ya-Li Ge; Xin-Li Wen; Xian-Ling Xiang (Hydrobiologia, 2019)

Archaeal community structure in sediments from a seamount in the Mariana Volcanic Arc - Wenyan Zhang; Jia Liu; Yi Dong; Xuegang Li; Cong Xu; Tian Xiao; Hongmiao Pan; Long-Fei Wu (Journal of Oceanology and Limnology, 2019)

Potassium Stimulation of IAA Transport Mediated by the Arabidopsis Importer AUX1 Investigated in a Heterologous Yeast System - Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Shih-Ming Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2019)

Mechanism of toppling and deformation in hard rock slope: a case of bank slope of Hydropower Station, Qinghai Province, China - Jun-chao Cai; Neng-pan Ju; Run-qiu Huang; Da Zheng; Wei-hua Zhao; Long-qi Li; Jian Huang (Journal of Mountain Science, 2019)

Shaking table test to assess seismic response differences between steep bedding and toppling rock slopes - Long-qi Li; Neng-pan Ju; Shuai Zhang; Xiao-xue Deng (Bulletin of Engineering Geology and the Environment, 2019)

Correction to: Seismic wave propagation characteristic and its effects on the failure of steep jointed anti-dip rock slope - Long-qi Li; Neng-pan Ju; Shuai Zhang; Xiao-xue Deng; Daichao Sheng (Landslides, 2019)

Seismic wave propagation characteristic and its effects on the failure of steep jointed anti-dip rock slope - Long-qi Li; Neng-pan Ju; Shuai Zhang; Xiao-xue Deng; Daichao Sheng (Landslides, 2019)

Positive PCNA and Ki-67 Expression in the Testis Correlates with Spermatogenesis Dysfunction in Fluoride-Treated Rats - Wen-peng Zhao; Hong-wei Wang; Jing Liu; Pan-pan Tan; Xiang-long Luo; Shi-quan Zhu; Xue-li Chen; Bian-hua Zhou (Biological Trace Element Research, 2018)

Transcriptome analysis to identify the Ras and Rap1 signal pathway genes involved in the response of TM3 Leydig cells exposed to zearalenone - Mingyang Wang; Nan Wang; Jingjing Tong; Jiawen Pan; Miao Long; Peng Li (Environmental Science and Pollution Research, 2018)

The primate extinction crisis in China: immediate challenges and a way forward - Baoguo Li; Ming Li; Jinhua Li; Pengfei Fan; Qingyong Ni; Jiqi Lu; Xuming Zhou; Yongcheng Long; Zhigang Jiang; Peng Zhang; Zhipang Huang; Chenming Huang; et al. (Biodiversity and Conservation, 2018)

Associations of HSP90AA2 gene polymorphisms with disease susceptibility, glucocorticoids efficacy and health-related quality of life in Chinese systemic lupus erythematosus patients - Man Zhang; Su-Su Li; Qiao-Mei Xie; Jian-Hua Xu; Xiu-Xiu Sun; Fa-Ming Pan; Sheng-Qian Xu; Sheng-Xiu Liu; Jin-Hui Tao; Shuang Liu; Jing Cai; Pei-Ling Chen; et al. (Genes & Genomics, 2018)

Regulation of H+-pyrophosphatase by 14-3-3 Proteins from Arabidopsis thaliana - Yu-Di Hsu; Yu-Fen Huang; Yih-Jiuan Pan; Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2018)

Fluorescent Carbon Dots as Cost-Effective and Facile Probes for Caffeic Acid Sensing via a Fluorescence Quenching Process - Qianqian Sun; Yuwei Long; Hongxi Li; Shuang Pan; Jidong Yang; Shaopu Liu; Xiaoli Hu (Journal of Fluorescence, 2018)

Effect of Electrospun Fibrous Scaffolds with Different Fiber Orientations on the Alignment of Microvessel-Like Structures - Zhenzhen Wu; Tao Yang; Chongyun Bao; Mingzheng Li; Hockin H. K. Xu; XueJuan Liao; Long Li; Ranran Huang; Jian Pan; Xian Liu (Journal of Medical and Biological Engineering, 2018)

Investigation of Perfluoroalkyl Substances (PFASs) in Sediments from the Urban Lakes of Anqing City, Anhui Province, China - Fasong Li; Hanyu Huang; Zhibing Xu; Hui Ni; Hao Yan; Ran Chen; Yan Luo; Wei Pan; Jinyun Long; Xiaofang Ye; Xiaofen Qian; Guangming Yu (Bulletin of Environmental Contamination and Toxicology, 2017)

Efficient and Product-Controlled Depolymerization of Lignin Oriented by Raney Ni Cooperated with Cs x H3 − x PW12O40 - Xiao-Jun Shen; Jia-Long Wen; Pan-Li Huang; Kai Zheng; Shuang-Fei Wang; Qiu-Yun Liu; Adam Charlton; Run-Cang Sun (BioEnergy Research, 2017)

Effectiveness of Fiber Bragg Grating monitoring in the centrifugal model test of soil slope under rainfall conditions - Long-qi Li; Neng-pan Ju; Yong-xing Guo (Journal of Mountain Science, 2017)

MicroRNA-146a Promotes Oligodendrogenesis in Stroke - Xian Shuang Liu; Michael Chopp; Wan Long Pan; Xin Li Wang; Bao Yan Fan; Yi Zhang; Haifa Kassis; Rui Lan Zhang; Xiao Ming Zhang; Zheng Gang Zhang (Molecular Neurobiology, 2017)

Modulation of Nav1.8 by Lysophosphatidic Acid in the Induction of Bone Cancer Pain - Hai-Li Pan; Ben-Long Liu; Wei Lin; Yu-Qiu Zhang (Neuroscience Bulletin, 2016)

Effect of the inclined weak interlayers on the rainfall response of a bedded rock slope - Long-qi Li; Neng-pan Ju (Journal of Mountain Science, 2016)

The effect of carbon nanotubes and titanium dioxide incorporated in PDMS on biofilm community composition and subsequent mussel plantigrade settlement - Jin-Long Yang; Yi-Feng Li; Xing-Pan Guo; Xiao Liang; Yue-Feng Xu; De-Wen Ding; Wei-Yang Bao; Sergey Dobretsov (Biofouling, 2016)

Molecular Cloning and Characterization of Two Genes Encoding Tryptophan Decarboxylase from Aegilops variabilis with Resistance to the Cereal Cyst Nematode (Heterodera avenae) and Root-Knot Nematode (Meloidogyne naasi) - Lin Li; Minghui Zheng; Hai Long; Guangbing Deng; Atsushi Ishihara; Feng Liu; Junjun Liang; Zhifen Pan; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

Physiological characterization of maize tolerance to low dose of aluminum, highlighted by promoted leaf growth - Liang Wang; Xian-Wei Fan; Jian-Long Pan; Zhang-Bao Huang; You-Zhi Li (Planta, 2015)

Transcriptome profiling of trichome-less reveals genes associated with multicellular trichome development in Cucumis sativus - Jun-Long Zhao; Yun-Li Wang; Dan-Qing Yao; Wen-Ying Zhu; Long Chen; Huan-Le He; Jun-Song Pan; Run Cai (Molecular Genetics and Genomics, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.

Comparative genomic analysis provides insights into the evolution and niche adaptation of marine M agnetospira sp. QH ‐2 strain - Boyang Ji; Sheng‐Da Zhang; Pascal Arnoux; Zoe Rouy; François Alberto; Nadège Philippe; Dorothée Murat; Wei‐Jia Zhang; Jean‐Baptiste Rioux; Nicolas Ginet; Monique Sabaty; Sophie Mangenot; et al. (Environmental Microbiology, 2014)
Summary Magnetotactic bacteria ( MTB ) are capable of synthesizing intracellular organelles, the magnetosomes, that are membrane‐bounded magnetite or greigite crystals arranged in chains. Although MTB are widely spread in various ecosystems, few axenic cultures are available, and only freshwater M agnetospirillum spp. have been genetically analysed. Here, we present the complete genome sequence of a marine magnetotactic spirillum, M agnetospira sp. QH ‐2. The high number of repeats and transposable elements account for the differences in QH ‐2 genome structure compared with other relatives. Gene cluster synteny and gene correlation analyses indicate that the insertion of the magnetosome island in the QH ‐2 genome occurred after divergence between freshwater and marine magnetospirilla. The presence of a sodium‐quinone reductase, sodium transporters and other functional genes are evidence of the adaptive evolution of M agnetospira sp. QH ‐2 to the marine ecosystem. Genes well conserved among freshwater magnetospirilla for nitrogen fixation and assimilatory nitrate respiration are absent from the QH ‐2 genome. Unlike freshwater M agnetospirillum spp., marine M agnetospira sp. QH ‐2 neither has TonB and TonB ‐dependent receptors nor does it grow on trace amounts of iron. Taken together, our results show a distinct, adaptive evolution of M agnetospira sp. QH ‐2 to marine sediments in comparison with its closely related freshwater counterparts.

Isolation and characterization of microsatellite loci in the short-tailed pit viper Gloydius brevicaudus (Viperidae) - Li Ma; Qing-Lin Tong; Ce Chen; Ying-Dan Pan; Long-Hui Lin (Conservation Genetics Resources, 2013)

Adaptation of spherical multicellular magnetotactic prokaryotes to the geochemically variable habitat of an intertidal zone - Ke Zhou; Wen‐Yan Zhang; Hong‐Miao Pan; Jin‐Hua Li; Hai‐Dong Yue; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2013)
Summary A combination of microscopic, molecular and biogeochemical methods was used to study the structure, phylogenetics and vertical distribution of spherical multicellular magnetotactic prokaryotes ( MMPs ) of intertidal sediments in the Y ellow S ea. These MMPs were 5.5 μm in diameter and composed of approximately 15–30 cells. They synthesized bullet‐shaped magnetites in chains or clusters. Phylogenetic analysis of 16 S rRNA gene sequences suggested that these MMPs represent a novel species affiliated to the D eltaproteobacteria. To study their vertical distribution and the relationship to geochemical parameters, sediment cores were collected after the redox potential was measured in situ . The sediments were composed of yellow, grey and black layers from the surface to depth. The spherical MMPs were concentrated near the grey‐black layer transition at a depth of 8–12 cm, while coccoid‐shaped magnetotactic bacteria near the yellow‐grey layer transition at a depth of 3–5 cm. The intertidal MMPs showed a deeper distribution at more reduced environments than coccoid‐shaped magnetotactic bacteria, and MMPs in lagoon sediments. Additionally the MMPs were concentrated significantly in layers with high proportion of fine sand and total organic carbon, rich in leachable iron but poor in nitrate. These results show an adaptation of spherical MMPs to the peculiar intertidal sediment habitat.

Association of CASP9, CASP10 gene polymorphisms and tea drinking with colorectal cancer risk in the Han Chinese population - He Liu; Xia Jiang; Ming-wu Zhang; Yi-feng Pan; Yun-xian Yu; Shan-chun Zhang; Xin-yuan Ma; Qi-long Li; Kun Chen (Journal of Zhejiang University-SCIENCE B, 2013)

Mechano growth factor (MGF) promotes proliferation and inhibits differentiation of porcine satellite cells (PSCs) by down-regulation of key myogenic transcriptional factors - Li-Li Qin; Xiao-Kui Li; Jian Xu; De-Lin Mo; Xiong Tong; Zhi-Cheng Pan; Jia-Qi Li; Yao-Sheng Chen; Zhe Zhang; Chong Wang; Qiao-Ming Long (Molecular and Cellular Biochemistry, 2012)

Construction of a high density integrated genetic map for cucumber (Cucumis sativus L.) - Wei-Wei Zhang; Jun-Song Pan; Huan-Le He; Chi Zhang; Zheng Li; Jun-Long Zhao; Xiao-Jun Yuan; Li-Huang Zhu; San-Wen Huang; Run Cai (Theoretical and Applied Genetics, 2012)

A novel genus of multicellular magnetotactic prokaryotes from the Yellow Sea - Ke Zhou; Wen‐Yan Zhang; Kui Yu‐Zhang; Hong‐Miao Pan; Sheng‐Da Zhang; Wei‐Jia Zhang; Hai‐Dong Yue; Ying Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2012)
Summary Multicellular magnetotactic prokaryotes (MMPs) are a group of magnetotactic microorganisms composed of 10–40 Gram‐negative cells. Currently, all the identified MMPs show a spherical morphology and synthesize mainly iron sulfide magnetosomes. In this study, we report a novel genus of MMPs with peculiar ellipsoidal morphology and iron oxide magnetosomes, which were discovered in intertidal sediment of the Yellow Sea in China. Optical and fluorescence microscopy revealed that this organism was ∼10 × 8 µm in size and composed of ∼40 cells enveloped by an outer layer. Scanning electron microscopy showed that the cells were arranged in 4–6 interlaced circles. Bullet‐shaped magnetite magnetosomes were organized in chains roughly parallel to the long axis of the ellipsoidal MMPs when analysed by transmission electron microscopy. These MMPs displayed special escape motility, i.e. swimming rapidly from the edge to the centre of the droplet and then slowly back to the edge. In addition, they exhibited negative phototaxis. Light microscopy observations showed that the ellipsoidal MMPs reproduced by division along the body long axis. Both analysis of 16S rRNA gene sequence and fluorescence in situ hybridization revealed the ellipsoidal MMPs as a new genus of the Deltaproteobacteria . In summary, this novel genus of MMPs exhibit unique morphology, peculiar division process and distinct phylogenetic affiliation compared with the other MMPs.

Development of a large-scale isolation chamber system for the safe and humane care of medium-sized laboratory animals harboring infectious diseases - Xin Pan; Jian-cheng Qi; Ming Long; Hao Liang; Xiao Chen; Han Li; Guang-bo Li; Hao Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

Efficient production of omega-3 fatty acid desaturase (sFat-1)-transgenic pigs by somatic cell nuclear transfer - DengKe Pan; Li Zhang; YanRong Zhou; Chong Feng; Chuan Long; Xiao Liu; Rong Wan; Jian Zhang; AiXing Lin; EnQiu Dong; ShuChen Wang; HouGang Xu; et al. (Science China Life Sciences, 2010)

TM4SF3 promotes esophageal carcinoma metastasis via upregulating ADAM12m expression - Zhuan Zhou; Yu-Liang Ran; Hai Hu; Jian Pan; Zhi-Feng Li; Li-Zhao Chen; Li-Chao Sun; Liang Peng; Xi-Lu Zhao; Long Yu; Li-Xin Sun; Zhi-Hua Yang (Clinical & Experimental Metastasis, 2008)

New Fluorescent Labels: 4- and 7-Chlorofluorescein - Feng-Yan Ge; Xi-Long Yan; Fan-Yong Yan; Hui-Ying Pan; Li-Gong Chen (Journal of Fluorescence, 2005)

Mutation analysis of hereditary multiple exostoses in the Chinese - L. Xu; J. Xia; H. Jiang; J. Zhou; H. Li; D. Wang; Q. Pan; Z. Long; C. Fan; H.-X. Deng (Human Genetics, 1999)